Symptomatic Focal Nodular Hyperplasiaduring Pregnancy : A Case Report (2004)
ABSTRACT: A 30-year-old woman presented with hepatomegalyand an audible hepatic bruit at 24 weeks gestation.Non-contrast MRI demonstrated an exophytic 12.6 x7.8 x 12.8 cm mass arising from the right lobe of theliver with a central scar, suggestive of focal nodularhyperplasia (FNH). Conservative management includ-ed monthly abdominal ultrasound examinations untilthe time of delivery, to assess growth of the mass andmonitor for risk of rupture. Seven weeks post partumthe patient experienced severe right upper quadrantpain. A CT angiogram of the liver demonstrated a sta-ble mass with no evidence of bleed or rupture andmultiple hypervascular masses throughout the liver.Surgical resection of the dominant lesion was per-formed. Histological examination of the lesion con-firmed FNH. The patient is now 22 months post sur-gery with radiographic evidence of stable multifocalFNH